2013
DOI: 10.1371/journal.pone.0061883
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor Plasticity after Music-Supported Therapy in Chronic Stroke Patients Revealed by Transcranial Magnetic Stimulation

Abstract: BackgroundSeveral recently developed therapies targeting motor disabilities in stroke sufferers have shown to be more effective than standard neurorehabilitation approaches. In this context, several basic studies demonstrated that music training produces rapid neuroplastic changes in motor-related brain areas. Music-supported therapy has been recently developed as a new motor rehabilitation intervention.Methods and ResultsIn order to explore the plasticity effects of music-supported therapy, this therapeutic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 45 publications
(69 reference statements)
6
74
1
1
Order By: Relevance
“…Jamali S 26. and Amengual J.L 27. in their experiment used healthy subjects as a comparator, and their conclusions supported the use of music-supported therapy for chronic stroke patients.…”
Section: Discussionmentioning
confidence: 70%
“…Jamali S 26. and Amengual J.L 27. in their experiment used healthy subjects as a comparator, and their conclusions supported the use of music-supported therapy for chronic stroke patients.…”
Section: Discussionmentioning
confidence: 70%
“…In this grid there were two perpendicular axes where the x -axis is horizontal and the y -axis is vertical (two-dimensional, Cartesian coordinate system). Stimulation sites were defined following x and y axes and becoming coordinates ( x, y ) in the grid (Amengual et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…Gains in motor function were accompanied by changes in motor cortex excitability (evaluated using motor mapping TMS) with an expansion of the cortical representation of the hand and by activation changes in fMRI (Rojo et al, 2011; Rodríguez-Fornells et al, 2012). In addition, Amengual et al (2013) have reported evidence from a group of chronic patients that have been treated with MST. Patients improved their motor function as well as an increase of the excitability of the motor system was encountered.…”
Section: Introductionmentioning
confidence: 99%
“…Superior motor control in daily activities is achieved with MST, as compared to conventional physical therapy (Schneider et al, 2007). Gains in motor skills by MST are related to increased ipsilesional MI excitability (Amengual et al, 2013; Grau-Sanchez et al, 2013), and the reinforcement of functional connectivity between auditory and premotor regions (Rodriguez-Fornells et al, 2012). Although mechanisms rendering the motor system sensitive to auditory priming and timing of stimulation still need to be elucidated, there is evidence suggesting that the time structure of music, namely the rhythm, is the essential element relating music specifically to motor behavior.…”
Section: Sensory-based Strategies To Enhance Post-stroke Motor Recmentioning
confidence: 99%